2015
DOI: 10.4049/jimmunol.1500232
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite Nuclear Localization Signal Controls Nuclear Import and DNA-Binding Activity of IFN Regulatory Factor 3

Abstract: Accurate cellular localization plays a crucial role in the effective function of most signaling proteins, and nuclear trafficking is central to the function of transcription factors. IFN regulatory factor (IRF)3 is a master transcription factor responsible for the induction of type I IFN, which plays a crucial role in host antiviral innate immune responses. However, the mechanisms for control and regulation of IRF3 nuclear import largely remain to be elucidated. In our study, we identified a bipartite nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 42 publications
(40 reference statements)
4
39
0
Order By: Relevance
“…4). Note that a small amount of IRF3 was detected in nuclei of unstimulated cells, probably reflecting IRF3 shuttling between the cytoplasm and nucleus (47). Interestingly, a similar trend was observed when cells expressed wild-type cFLIP L : there were no visual differences in nuclearly localized IRF3 in unstimulated versus stimulated cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Note that a small amount of IRF3 was detected in nuclei of unstimulated cells, probably reflecting IRF3 shuttling between the cytoplasm and nucleus (47). Interestingly, a similar trend was observed when cells expressed wild-type cFLIP L : there were no visual differences in nuclearly localized IRF3 in unstimulated versus stimulated cells.…”
Section: Resultsmentioning
confidence: 99%
“…This is currently under investigation in our lab. IRF3 is shuttled from the nucleus to the cytoplasm due to the presence of NLSs and NESs (47). Here, we find that cFLIP L inhibits the action of a dimerized phospho-mimetic form of IRF3 (IRF3CA) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IRF3 is an important transcription factor in cells. Its regulation of cell functions depends on the nuclear import level of this protein [35]. In this study, we found that the expression and secretion of the cytokine IFN-β was decreased with the down-regulation of the IRF3 protein level in the nucleus after IRF3 gene silencing in KCs by the interference adenovirus.…”
Section: Discussionmentioning
confidence: 76%
“…Because the major function of IRF3 is in IFN production, it is thus speculated that the NPHK motif and changes associated with the D → N substitution in IRF3 may facilitate IFN production for aquatic species, specifically through modulations of DNA bindings. In addition, the DPHK (positions 102-105) of human IRF3 is located between nuclear localization (77-89) and nuclear export (139-149) signals [47][48][49][50] . Therefore, although the DPHK motif is conserved among vertebrate species and its substitution to NPHK in three groups of animals is all associated with aquatic life, the exact biological functions of the motif need further experimental exploration.…”
Section: Discussionmentioning
confidence: 99%